Vibrational Heat Transfer Intensification in an Annulus with a Deformable Boundary - Nikolai Kozlov (Shock and Vibration)
An experimental study is carried out on heat transfer in a horizontal liquid annulus at boundary oscillations. The inner boundary is formed by a copper rod that is heated using electric current. The outer boundary is made of an elastic silicone tube brought to oscillations by two electrodynamic vibrators situated symmetrically on the opposite sides. In the absence of vibrations, a classic natural convection is observed. Vibrations excite steady time-average flows in the fluid. The steady flows make the gravity-induced flow structure transform, and the heat transfer is intensified. In the analysis, it is shown that the heat transfer in the studied system is determined by a competition between the natural convection and steady streaming. A domain of parameters is found where the latter dominates.